Theory and Practice of Participatory Approach in Schools: an Example of the Future Youth Schools – a Forums Project - Jarkiewicz, Anna (Participatory Social Work: Research, Practice, Education, 2019)
The active participation of youth has indeed become a key theme across a broad range of service delivery. All organisations concerned with children and young people now promote participation as a “central issue” (Wright, Haydon, Morgan, 2002). Across the EU there is a need to increase educational attainment and active civic participation by European youth. FYS-Forums is responding to this by creating a model for school – led global citizenship youth forums. But even the most carefully planned project can run into unexpected issues. In my contribution a critical review of FYS-FORUM project will be presented.